Ecofriendly lignocellulose pretreatment to enhance the carboxylate production of a rumen-derived microbial consortium. (July 2017) - Lazuka, Adèle; Roland, Cécile; Barakat, Abdellatif; Guillon, Fabienne; O'Donohue, Michael; Hernandez-Raquet, Guillermina
Highlights: Dry chemo-mechanical pretreatments impact biomass crystallinity and macroporosity. Dry chemo-mechanical pretreatment increased the carboxylate production rate by RWS. Dry chemo-mechanical pretreated biomass enhances the microbial xylanase activity. Initial biomass macroporosity correlated with the biological acidogenic potential. Abstract: Innovative dry chemo- and chemo-mechanical pretreatments form an interesting approach for modifying the native physico-chemical composition of lignocellulose facilitating its microbial conversion to carboxylates. Here, the impact of four dry-pretreatment conditions on the microbial transformation of wheat straw was assessed: milling to 2 mm and 100 µm, and NaOH chemical impregnation at high substrate concentrations combined with milling at 2 mm and 100 µm. Pretreatment effect was assessed in the light of substrate structure and composition, its impact on the acidogenic potential and the major enzyme activities of a rumen-derived microbial consortium RWS. Chemo-mechanical pretreatment strongly modified the substrate macroporosity. The highest carboxylate production rate was reached after dry chemo-mechanical treatment with NaOH at 100 µm. A positive impact of the dry chemo-mechanical treatment on xylanase activity was observed also. These results underline that increasing substrate macroporosity by dry chemo-mechanical pretreatment had a positive impact on the microbial acidogenic potential.